ASSESSING DIGITAL-HISTORICAL LITERACY AND CRITICAL THINKING AMONG HISTORY STUDENTS (Education in the 21st Century, 2025)
This study empirically examined the proficiency levels of History students at Yerevan State University (YSU) in Critical Historical Thinking Competence (CHTC) and Digital-Historical Literacy (DHL). The research addresses the limited availability of empirical assessments of historical-thinking competencies and examines a local institutional challenge at YSU — the integration of externally produced academic research into teaching practice — through measurable indicators of critical-historical and digital-historical literacy. A Convergent Parallel Mixed Methods design was employed, involving a quantitative cohort of 150 students (N=150) and a qualitative cohort of 20 participants (N=20). Data were collected using performance-based CHTC assessments and a customized Digital-Historical Literacy Scale (D-HiLS), augmented by semi-structured interviews.Quantitative analysis revealed that undergraduate students (n = 97) scored lower on argumentative synthesis tasks (M = 2.73, SD = 1.24) compared to graduate students (n = 53; M = 3.68, SD = 0.92), t≈4.8, p
Keywords: historical thinking; digital-historical literacy; critical source evaluation; mixed methods research; quantitative–qualitative integration; educational measurement validity; Armenian higher education; pedagogical innovation